OPTIMISING INVESTMENT IN THE ENERGY SECTOR IN DEVELOPING COUNTRIES IN SOUTH EAST EUROPE - Vladisavljević, Vladan; Ristić, Dejan; Obrić, Bojan; Mičić, Saša; Lazić, Snežana; Jakovljević, Sanja; Mirković, Spasenija; Praća , Nebojša (Economics of Agriculture, 2024)
In this paper we are researching the optimality of developing counties for investing in their energy sector as a way of diversifying portfolio by applying the multicriteria decision making model There are multiple quantitative and qualitative criteria that can be considered when finding the adequate market for investment, other than its natural potential, such as the level that its energy sector is developed, legal framework that surrounds this sector, market openness of the observed economy, ease of investment and market liquidity. The four sources of the energy sector that are considered are oil, gas, coal and renewable energy sources. Even though the renewable energy sources aren’t sufficiently exploited, the countries that have high potential could provide significant financial profits by exploiting them.